BOOSTING BRAND AWARENESS AND SALES PERFORMANCE OF TUBBLE B.V. WITH THE USE OF DIGITAL MARKETING WITHIN THE NETHERLANDS - Yunan Arestu Prananca; Harjum Muharam (Diponegoro Journal of Management, 2022)
Tubble is an international startup company that is operating in the bathing industry. It specialised in selling inflatable bathtubs which became its main source of income and its main product. As a business, Tubble operates as an e-commerce which means that all its business operations are done via online means, and it mainly sells in the online market. Based on the discussion with the CEO of Tubble, Tubble is currently facing some stagnation in its digital marketing capability and sales within the Dutch market. Due to the stagnation in the digital marketing capability, several marketing interns were appointed to provide solutions to the marketing capability of Tubble. Furthermore, as one of the main market operations of Tubble, having stagnant sales and no growth in recent times is bad for the company’s overall performance. There is no noticeable growth of sales within the market which becomes a problem. Tubble wants to boost its digital marketing capability which will ultimately lead to increased brand awareness and sales performance